Investigation of the elements of Rho (Rop) GTPase-depent signalling in Medicago sp. : identification of Rop guanine nucleotide exchange factors (ROPGEFs) in Medicago truncatula - Dunainé Fodor, Csilla; Fehér, Attila (Acta Biologica Szegediensis, 2008)
Rop GTPase-dependent signalling plays a significant role in plant development as well as during the responses of plants to environmental signals. The elements of these diverse signalling pathways just started to be revealed during the last couple of years, especially in Arabidopsis thaliana. In our laboratory we aim to identify these elements from the model species Medicago truncatula in order to allow investigations of Rop GTPase-mediated signalling during Medicago-Sinorhizobium symbiosis and somatic embryogenesis. Here we report on the in silico identification of seven Rop guanine nucleotide exchange factor (RopGEF) sequences and their primary characterization including gene expression profiling in various plant organs.